SPECIATION FEATURES OF GOLD IN ORES AND MINERALS OF THE NATALKINSKOE DEPOSIT (NORTH-EAST RUSSIA) - R. G. Kravtsova; A. S. Makshakov; V. L. Tauson; O. Yu. Belozerova; V. V. Tatarinov (Геодинамика и тектонофизика)
The distribution and speciation features of gold in ores and minerals of the Natalkinskoe gold deposit (North-East Russia) are studied using light microscopy (LM), scanning electron microscopy with energy dispersive X-ray spectrometry (SEM-EDX), X-ray electron probe microanalysis (EPMA), "phase" chemical analysis with atomic absorption spectrometry (PCA-AAS) and atomic absorption spectrometry with analytical data selections for single crystals (AAS-ADSSC). The vein and streaky-vein ores are high-grade ores, whereas veinlet-disseminated ores are less rich and disseminated ores are poor in gold. Up to 85 % of the gold in the ores is in a free native state, associated with quartz and sulfide minerals. LM, SEM-EDX and EPMA reveal that the predominant gold grains are 0.01 to 2.00 mm in size and at a fineness of 720 to 900 ‰. The finely dispersed and submicron elemental gold particles (Au0) amounted to 20 % and are mainly enclosed into arsenopyrite and pyrite. According to PCA-AAS data, the highest Au concentrations (up to 1383 ppm) are recorded in arsenopyrite; lower contents are typical of pyrite (up to 158.2 ppm). In these sulfides, two non-mineral species of "invisible" Au are the structurally bound and surface-bound species recognized by AAS-ADSSC. The structural Au is included in the mineral structure. The surface-bounded Au prevails and is confined to nano-sized, non-autonomous phases (NAPs) on the sulfide surface. In common with "invisible" Au, the micro-sized particles of native gold are often observed on the surface and within the surface layers of sulfide crystals. This is consistent with the model of post-growth transformations of nano-sized NAPs, resulting in the formation of nano and micro-sized Au0 particles. It is expected that the major part of gold contained in arsenopyrite and pyrite as finely dispersed and submicron particles, as well as the surface-bound gold in NAPs, can be won with modified current schemes of gold concentration, which enhances the value of the gold ore mining.